BEYOND THE FILTER: INTERSECTIONALITY AND THE EXPERIENCE OF BLACK TEENS IN RECIFE ON INSTAGRAM (TEL Tempo, Espaço e Linguagem, 2024)
This article aims to reflect on the itineraries of black teenagers on Instagram, emphasizing their online experiences. To do so, we start from the assumption that all discursivity is historicized and territorialized and, for specific groups, as is the case of black women, an additional component is present in their lives: intersectionality. Semi-structured interviews and digital ethnography were the ways to seek an understanding of the narratives that make up their biographies, which were read under the magnifying glass of feminist thinkers. Thus, the powerful voices of teenagers and intellectuals denounce the ideas of perfection and loneliness that populate the digital environment and subjectivities. Keywords: Teenager. intersectionality. Digital Social Networks. Race.